From Pop and Premodern Celebrities: Towards a “Zombie Democracy” - Rincón, Omar (2017)
This essay begins at the cultural capitals of today’s citizens in order to understand politics and make sense of it in the present times. There are three types of citizens: critics and cynics, who feel their consumption is counter-culture, who have networks as temples, who believe and disbelieve in politics; premodern citizens, who adjust their affections to their beliefs and turn their anger into a moral battle; modern citizens, who believe in ideas, parties, freedoms, institutions, rights. In this context it is understood why today our politicians are celebrities, pop intellectuals, practitioners of CEOcracy and religious and nationalist value oriented. It is said that political communication in the twenty-first century is an illegitimate craft that combines pre-modern morality with coolture, which has led democracy to become a zombie concept.